Age estimation by DNA methylation levels in Iraqi subjects - Al-Ghanmy, Hiba S.G.; Al-Rashedi, Nihad A.M.; Ayied, Asaad Y. (Gene reports, 2021)
Epigenomic studies suggest that DNA methylation profiles can indicate chronological age, which is essential in forensic investigation. Here, we analyzed DNA methylation at CpG sites in five genes to investigate their potential to predict human age. Human blood DNA samples, obtained from Iraqi subjects, were subjected to bisulfite conversion and pyrosequencing of 27 CpG sites located in the ELOVL2, TRIM59, KLF14, FHL2, and MIR29B2CHG genes. An age prediction model based on multivariate regression analysis and leave-one-out cross-validation (LOOCV) was built using the three highest age-correlated loci present in ELOVL2, TRIM59, and KLF14 genes, which provided a mean absolute deviation of 4.85 and 5.17, and root mean square error of 5.69 and 6.58 years. The results of ANOVA suggest that there is no significant difference between DNA methylation levels of males and females in the five genes. Finally, the new set of three methylated CpG markers is capable of producing an accurate age-predicted model of blood samples. Predicted age correlated well with chronological age in the 18–39 and 40–59 year age categories, but less accurately in the ≥60 year age category. •Epigenetic markers can indicate a correlation with chronological age in an Iraqi population.•The best three CpG sites in ELOVL2, TRIM59, and KLF14 genes were tested to predict chronological age.•MAD and RMSE between the predicted and the observed ages was 4.85 and 5.17, and 5.69 and 6.58 years, respectively.